Construction of Operation Portraits Based on a Cloud Model for Power Distribution Networks - Liang, Jifeng; Li, Tiecheng; Fan, Hui; Hu, Xuekai; Wang, Lei; Jiang, Shan (Frontiers in Energy Research, 2022)
With the high proportion of new energy access in power distribution networks, the operation of distribution networks become more uncertain and complex. How to extract features that embodies the full perspective of distribution network from the diverse and varying conditions is of great significance to master the operating property of distribution networks under the high proportion of new energy. This paper investigates portraits construction of power distributions. A data-driven method of portraits construction for distribution network based on cloud model is proposed. Firstly, the indexes describing operation of Medium Voltage Distribution Network (MVDN) as well as Low Voltage Station Area（LVSA）is established. By means of statistics, fuzzy label templates are provided for the indexes. Then, extract the practical indexes from MVDN operation data of days as a collected sample, which is used as a droplet of the cloud model. The whole droplets of all days were input to the reverse cloud generator to generate fuzzy parameters representing the overall behavior. Finally, scores of operating properties were obtained through weighted sum according to fuzzy distance of the parameters and the label templates. Therefore, a group of portraits describing MVDNs with clear physical and objective meaning are constructed.